Measuring the benefits to advertising under monopolistic competition - Boland, Michael A.; Crespi, John M.; Silva, Jena; Xia, Tian (My University, 2012)
This paper determines the benefits and costs of firm-level advertising in a monopolistically competitive industry. The model is useful in an environment in which firm-level costs may be absent or imprecise. The empirical example uses data on the advertising for a new line of prune snacks by Sunsweet Growers between 2008 and 2010, revealing average benefit-cost estimates from $1.26 to $4.35 for every dollar allocated to the new product line.
Keywords: Advertising; Benefit-cost analysis; Industrial organization; Monopolistic competition; Agricultural marketing